Percepción del bienestar de los funcionarios de un asilo en relación con las tareas del cuidado al adulto mayor. (2022)
he present investigation was carried out with the purpose of determining the perception of the emotional well-being of the workers of the nursing home of the city of Tunja regarding the tasks of care for the elderly. This study was carried out within a descriptive qualitative research, its importance is focused because currently nursing homes require workers; capable, with commitment to carry out daily tasks, but above all with excellent emotional well-being, since maintaining good emotional well-being is important for the productivity of tasks.